2022
DOI: 10.3390/mti6060046
|View full text |Cite
|
Sign up to set email alerts
|

The Quantitative Case-by-Case Analyses of the Socio-Emotional Outcomes of Children with ASD in Robot-Assisted Autism Therapy

Abstract: With its focus on robot-assisted autism therapy, this paper presents case-by-case analyses of socio-emotional outcomes of 34 children aged 3–12 years old, with different cases of Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD). We grouped children by the following characteristics: ASD alone (n = 22), ASD+ADHD (n = 12), verbal (n = 11), non-verbal (n = 23), low-functioning autism (n = 24), and high-functioning autism (n = 10). This paper provides a series of separate quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
0
11
0
2
Order By: Relevance
“…However, long-term exposure appears to be beneficial. While some studies show a decrease in eye contact with the robot throughout the interaction [29,180], others highlight that the improvement in behavior is maintained over several sessions [47,246] or even increases as children show more and more engagement in the activity as time goes on [26,202]. This benefit would be all the greater for children with the most severe autistic symptoms, compared with peers with a mild to moderate form of autism [202].…”
Section: Methodological Limitationsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, long-term exposure appears to be beneficial. While some studies show a decrease in eye contact with the robot throughout the interaction [29,180], others highlight that the improvement in behavior is maintained over several sessions [47,246] or even increases as children show more and more engagement in the activity as time goes on [26,202]. This benefit would be all the greater for children with the most severe autistic symptoms, compared with peers with a mild to moderate form of autism [202].…”
Section: Methodological Limitationsmentioning
confidence: 99%
“…It is therefore important to take them into account when analyzing the results. Similarly, in individuals with ASD, the appearance of the robot [167], the profile of the child [202], and the intervention context can also have an impact on the interaction.…”
Section: Current Challenges In the Interaction Of Autistic Individual...mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, articles were found that did not perform robotic therapy but provided advanced insights into the technologies used (algorithms) in therapies for autistic children from different articles [ 42 ], the ethical and social aspects of robot-assisted therapy [ 43 ], and the socio-emotional outcomes of robot-assisted therapy [ 44 ], providing valuable information on the expectations and ethical acceptability of this new form of intervention.…”
Section: Introductionmentioning
confidence: 99%